Assessing Customer Satisfaction and Loyalty in the Energy Sector Through Service Quality: A Modified SERVQUAL Analysis - Çiçeklidağ, Pasa; Nebati, Emine Elif; Gülen, Kemal Güven; Zaim, Selim; Nebati, Emine Elif (Springer, 2025)
This study examines the impact of service quality on customer satisfaction and loyalty in the energy sector using the SERVQUAL model. Key dimensions such as reliability, empathy, and physical features were found to significantly influence customer satisfaction. The research involved an online survey, with data analyzed using Structural Equation Modeling (SEM) to identify both direct and indirect effects of service quality dimensions on customer satisfaction and loyalty. Results show that improving reliability and empathy can notably enhance customer satisfaction, leading to stronger customer loyalty. However, the study acknowledges limitations, such as the generalizability of results due to the online nature of the survey and the study's focus on a specific geographical region. The use of verbal data may also introduce bias, which future research could address by applying more detailed data collection methods and examining sub-factors. The study concludes that energy companies should refine their service strategies to better meet customer expectations, suggesting further research in different regions and sectors.
24th International Symposium for Production Research, ISPR 2024 / Editors:Numan M. Durakbasa, Kemal Güven Gülen -- Springer -- ISBN:978-303183610-7 -- 2025.
Keywords: Customer satisfaction; Energy sector; Loyalty; Service quality; SERVQUAL; Sustainability